Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1515/cclm.2003.197
|View full text |Cite
|
Sign up to set email alerts
|

Two MMP-2 Promoter Polymorphisms (–790T/G and –735C/T) in Chronic Heart Failure

Abstract: Remodelling of extracellular matrix by activated matrix metalloproteinases is considered to contribute to progression of ventricle remodelling during chronic heart failure. The aim of this study was to associate two promoter polymorphisms, -790T/G and -735C/T, in the gene for matrix metalloproteinase (MMP)-2 (gelatinase A) with chronic heart failure (CHF). For this purpose, 164 patients (124 men, 40 women, median age 56 years, range 21-91 years) with CHF (functional class NYHA II-IV, ejection fraction median 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Contrarily Vasku et al [18] had found that variant allele frequency of the -735C [ T MMP-2 polymorphism was significantly higher in patients with chronic heart failure than in subjects without clinical signs of cardiovascular disease. Cotignola et al [19] reported patients with esophageal squamous cell carcinoma carrying the -735CC genotypes had an increased risk of developing cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily Vasku et al [18] had found that variant allele frequency of the -735C [ T MMP-2 polymorphism was significantly higher in patients with chronic heart failure than in subjects without clinical signs of cardiovascular disease. Cotignola et al [19] reported patients with esophageal squamous cell carcinoma carrying the -735CC genotypes had an increased risk of developing cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The MMP‐2 and MMP‐9 polymorphisms (−735C > T) and (−1562C > T) were genotyped in subjects using polymerase chain reaction (PCR)‐restriction fragment length polymorphism. Primers for amplification of MMP‐1 (−1607 2G > 1G) and MMP‐3 (−1612 5 A > 6 A) were taken as described previously . PCR was performed in a total volume of 25 μl with 15 pmol of each primer, genomic DNA (100–150 ng), 10 mM deoxynucleotide triphosphates, PCR buffer containing 100 mM Tris–HCl (pH 8.6), 50 mM KCl, 1.5 mM MgCl 2 and 1.5 units of Taq polymerase (Bangalore Genei, Bengaluru, India).…”
Section: Methodsmentioning
confidence: 99%
“…39 Similarly, the −790 T/G MMP-2 polymorphism, in addition to the −735 C/T polymorphism, also associates with chronic heart failure in patients from the Czech Republic. 40 How these polymorphisms effect heart failure related deaths is still unclear.…”
Section: Mmps As Biomarkers For Heart Failurementioning
confidence: 99%